Pengaruh Giberelin Dan Temperatur Terhadap Pertumbuhan Semai Gandaria (Bouea macrophylla Griffith.) - Hermalina Sinay (Universitas Lambung Mangkurat, 2011)
Gandaria (Bouea macrophylla Griffith), is one of the fruit plants belongs to family Anacardiaceae. Young fruits of gandaria are normally consumed as salad, while mature fruits are consumed as fresh fruit or juice. Recently, the population of gandaria is getting less due to people activity of cutting trees for housing. On the other hand, this activity is not followed by replanting new plants for maintaning this species. Naturally, the seed of gandaria can germinate and grow, but its growth is slow. Treatments with cold or warm stratification, acid and organic solution or growth hormones can be applied to promote germination. Gibberellins is one of growth hormones that can promote seed germination. The objectives of this research were to study the effects of gibberellins and temperature on seedling growth of gandaria. Samples used in this research were mature fruits of gandaria taken from Lateri Ambon. Variables measured were the speed of seedling emergence, plant height, and leaf number. Factorial pattern of complete randomized block design was used in this research with the first factor were gibberellins concentrations which consist of 4 levels 0 ; 0,2 ; 0,4 and 0,8 ppm , and the second factor were temperature which consist of 3 levels 40C, 290C and 370C, each combination treatment with three replication. Data were analyzed using analysis of variance and followed by Duncan multiple range test (DMRT) at the significant level of 5%. The results showed that gibberellins and temperature significantly increased the speed of seedling emergence, plant height, and leaf number with the highest value obtained in 0,2 ppm gibberellin at temperature 4oC treatment. The highest value of seedling emergence was obtained in 0,4 ppm of gibberellins concentration at temperature 40C treatment. It can be concluded that the best quality and quantity of seedling was obtained in treatment of 0,2 ppm gibberellin concentration at temperature 4oC .